Corporate entrepreneurship [ how to create a thriving entrepreneurial spirit throughout your company - Hisrich, Robert D.; Kearney, Claudine (McGraw-Hill, 2012)
A practical approach to one of the hottest trends in business today--creating entrepreneurial ventures within large companies to combat increased competition online and abroad